Hubungan Derajat Preeklampsia terhadap Kadar Ldh di RSUD Abdul Moeloek Provinsi Lampung Periode Januari-Desember 2018 - Ayu Agustira; Putu Ristyaning Ayu S; Ety Apriliana (Yayasan Literasi Sains Indonesia, 2022)
In preeclampsia, there is a proof that endothelial cells and changes in endothelial cell function hold an important role in the pathogenesis of preeclampsia. LDH serum is an important part of the evaluation of tissue damage associated with endothelial damage. Endothelial dysfunction contributes to inappropriate vasoconstriction and platelet aggregation which is an early sign of hypertension. LDH serum was found to be increased in mild and severe preeclampsia women compared to normal pregnant women in the third trimester but LDH serum values were significantly increased in women with severe preeclampsia. This study was aimed to find the relation between LDH levels and the degree of preeclampsia in RSUD Dr. H. Abdul Moeloek Lampung Province. This study used the data that is collected from medical records of patients with mild preeclampsia and severe preeclampsia who were treated in RSUD Dr. H. Abdul Moeloek on January to December, 2018. The sampling method used was Simple Random Sampling. The results showed that the average LDH level in pregnant women who had mild preeclampsia was 518.88 IU / L, whereas in pregnant women who had severe preeclampsia was 695.02 IU / L. The relation of the degree of preeclampsia to LDH levels using Mann-Withney test with the p value obtained was 0.032, which means p <0.05.